Covalently trapping MutS on DNA to study DNA mismatch recognition and signaling - Heinze, Roger J.; Sekerina, Svetlana; Winkler, Ines; Biertuempfel, Christian; Oretskaya, Tatiana S.; Kubareva, Elena; Friedhoff, Peter; Justus Liebig University Giessen (My University, 2012)
The DNA repair protein MutS forms clamp-like structures on DNA that search for and recognize base mismatches leading to ATP-transformed signaling clamps. In this study, the mobile MutS clamps were trapped on DNA in a functional state using single-cysteine variants of MutS and thiol-modified homoduplex or heteroduplex DNA. This approach allows stabilization of various transient MutS-DNA complexes and will enable their structural and functional analysis.
Keywords: ddc:570